DIGITAL MARKETING SEBAGAI STRATEGI PENGEMBANGAN PASAR PADA UMKM DI KELURAHAN RUNGKUT MENANGGAL - Purwanto, Eko; Wulandari, Ricy Inaiyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2023)
Micro, Small, Medium Enterprises (MSMEs) prove their role for the economy in Indonesia. It is proven from MSMEs that even though they are only a micro, small, medium enterprise can help the family economy in Indonesia. However, there are still various problems that exist in MSMEs, namely limitations in business capital, mastery of science and technology which generally have an impact on unclear business prospects. Therefore, provisions were given to the people of Rungkut Menanggal Village regarding marketing to local MSMEs to provide an overview of marketing so that they are able to survive in the market and develop even better by paying attention to how to market products.